Simultaneously suppressing lithium dendrite growth and Mn dissolution by integration of a safe inorganic separator in a LiMn2O4/Li battery. Issue 7 (3rd February 2020) - Rao, Zhixiang; Yang, Ze; Gong, Wenzhe; Su, Shang; Fu, Qiuyun; Huang, Yunhui
Abstract : Inorganic separator hydroxyapatite nanowires are designed to inhibit lithium dendrites growth and metal dissolution simultaneously in lithium transition metal oxide/Li battery. Abstract : Lithium metal is considered an ideal anode material for next-generation rechargeable batteries with high energy density due to its high theoretical capacity and the lowest electrode potential among metals. However, the practical application of Li metal coupled with some traditional cathode materials like spinel LiMn2 O4 is hindered by Li dendrites on the anode surface and the dissolution of metal (Mn) ions in the electrolyte. In this work, we introduce a safe inorganic separator based on hydroxyapatite (HAP) nanowires into a LiMn2 O4 |Li battery. The HAP separator can not only suppress Li dendrite growth, but also help to reduce Mn-ion dissolution, which dramatically improves the cycle stability and safety of the battery. The improved mechanism is carefully investigated. With the integration of the safe inorganic HAP separator, high energy density batteries with Li metal anodes coupled with LiMn2 O4 or other cathode materials are promising for practical application.